Copra meal hydrolysis by the recombinant β-mannanase KMAN-3 and MAN 6.7 expressed in Escherichia coli - Sritrakul, Nipat; Nitisinprasert, Sunee; Keawsompong, Suttipun (3 Biotech, 2020)
Hydrolysis products of defatted copra meal (DCM) hydrolysis were investigated with either recombinant β-mannanases from Klebsiella oxytoca KUB-CW2-3 (KMAN-3) or Bacillus circulans NT 6.7 (MAN 6.7). Morphological changes and functional groups of solid residues were also determined by scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) spectroscopy. Results revealed that the Michaelis–Menten constant ( K m ) and maximum velocity ( V max ) values of KMAN-3 on DCM were 2.4 mg/ml and 5.4 U/mg, respectively, while MAN 6.7 recorded K m and V max at 2.0 mg/ml and 4.3 U/mg, respectively. Both enzymes efficiently randomly hydrolysed DCM and produced a range of different manno-oligosaccharides (MOS). The profile of hydrolysis products was different for each enzyme used. Main products from hydrolysis of DCM by KMAN-3 and MAN 6.7 were various MOS including mannobiose (M2), mannotriose (M3), mannotetraose (M4), and mannose, whereas mannopentaose (M5) was only found from KMAN-3. Amount of M3 produced by KMAN-3 was about three times higher than from MAN 6.7. Total MOS yield for KMAN-3 was 1.5-folds higher than for MAN 6.7. SEM analysis showed that enzymatic hydrolysis with KMAN-3 and MAN 6.7 resulted in deconstruction of the DCM structure which generated a variety of MOS products. FTIR spectra revealed that the properties of both hydrolysed solids were not significantly different compared to the original DCM. Results suggested that KMAN-3 was a promising candidate for production of high MOS content from copra meal.